STUDY OF ENVIRONMENTAL AWARENESS AMONG ELEMENTARY SCHOOL TEACHERS (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Environment is a multi dimensional system of complex relationship in a continuing state of change. By environment we mean not only our immediate surroundings but also a variety of issues connected with human activity, productivity, basic living and its impact on natural resources such as land, water, atmosphere, forests, dams habitat, health, energy resources etc.